HAND CRAFTS MATERIALS OF CLAY (STUDY OF HOUSEHOLD IN BUMI JAYA VILLAGE CIRUAS DISTRICT SERANG) - Adih Supriadi; Vera Maria; Eloh Bahiroh (JURNAL MANAJEMEN DAN BISNIS, 2020)
The home industry is a home business that produces various commodity products that are processed manually or using simple production machines. One of the home industry centers in Serang Regency is clay handicrafts that have been around for a long time, mostly women. During their development, they still experience many problems, especially in terms of production and marketing. Based on this, the authors researched to analyze the production and marketing aspects of clay crafts. The population and samples taken were fifteen people, they were clay craftsmenin Bumi Jaya Village, Serang Regency. This is done to find out the various aspects of production and marketing they have been doing related to the clay crafts they are doing. The sampling was carried out through direct observation with the clay crafts actors. Based on the results of research that has been carried out, production and marketing can still be done, and it is just that what needs special attention is that marketing must be further improved and expanded, which so far only relies on consumer visits to show rooms and waiting for special orders from consumers.